CREATIVE DECEPTIONS: TELEVISION SOAPS AND WOMEN’S BODIES IN BAHIA - Gunner, Liz (PINS-Psychology in Society, 2025)
Brown, Lisa Beljuli (2011) Body parts on Planet Slum: Women and television in Brazil. London: Anthem Press. (Key issues in Modern Sociology.) ISBN 978-0-85728-797-7 hbk; also available as an eBook. Pages xxv + 156. As its rather bleak title suggests, this is not a book for the faint-hearted. It is though a powerful text which attempts to understand why women in the slums of Salvador in the state of Bahia, Brazil, adore watching telenovelas almost to the point of obsession. Lisa Brown turns firmly away from a reading of the telenovelas as redemptive fantasy (Modleski, 1982; and see Modleski, 1983). Neither does she give an analysis that allows for the emergence of a nationalist idea of belonging spun from “the magic of television and film stars” (Abu-Lughod, 2005: 228). Rather she demonstrates that the diet of telenovelas destroys and yet sustains the women who constitute the poorest of the urban poor in the most “African” of Brazil’s provinces. Brown’s study is based on a year’s fieldwork in two of Salvador’s biarros in 1999 and 2000. During this time she lived close to the women whose lives she studied, became acquainted with their families, neighbours, the rhythm of their lives and with the visual texts and narratives which absorbed and in a sense dominated them. Eschewing a more standard anthropological telling, Brown opts instead for a fictive recreation, interlaced with theoretical explanation. This approach works well most of the time but can be heavy-handed, so that at moments her theoretical framing seems intrusive and her insistence on the three alienated “body parts” of her women subjects: the vagina, the womb and the back intrudes too heavily.